Implementation of the Mixed Ecology in Church of England Diocesan Strategies - Dunlop, Andrew (Ecclesial Futures, 2025)
The mixed-ecology is a term that has come to denote both traditional and new forms of church mutually flourishing alongside one another, and since 2021 is included as part of the vision and strategy of the national Church of England. The extent to which this thinking has permeated the Church of England strategy varies greatly by dioceses and is affected both by use of language and national funding. The strategies which flowed from the twin streams of starting contextual forms of church (such as fresh expressions) and planting more congregations that are more identifiable as church (such as resource churches) now exhibit similar qualities. This article is based on a survey of diocesan strategies and vision statements and publicly available documentation from 40 of the 42 dioceses of the Church of England. I argue that diocesan strategies have been converging towards those that could be described as ‘mixed ecology’ even before the national strategy was adopted, and I highlight some present implications of the adoption of mixed ecology since then.